Fetal glucocorticoid receptor (Nr3c1) deficiency alters the landscape of DNA methylation of murine placenta in a sex-dependent manner and is associated to anxiety-like behavior in adulthood - Schmidt, Michaela; Lax, Elad; Zhou, Rudy; Cheishvili, David; Ruder, Arne Mathias; Ludiro, Alessia; Lapert, Florian; Macedo da Cruz, Anna; Sandrini, Paolo; Calzoni, Teresa; Vaisheva, Farida; Brandwein, Christiane; et al. (Translational Psychiatry, 2019)
Prenatal stress defines long-term phenotypes through epigenetic programming of the offspring. These effects are potentially mediated by glucocorticoid release and by sex. We hypothesized that the glucocorticoid receptor (Gr, Nr3c1) fashions the DNA methylation profile of offspring. Consistent with this hypothesis, fetal Nr3c1 heterozygosity leads to altered DNA methylation landscape in fetal placenta in a sex-specific manner. There was a significant overlap of differentially methylated genes in fetal placenta and adult frontal cortex in Nr3c1 heterozygotes. Phenotypically, Nr3c1 heterozygotes show significantly more anxiety-like behavior than wildtype. DNA methylation status of fetal placental tissue is significantly correlated with anxiety-like behavior of the same animals in adulthood. Thus, placental DNA methylation might predict behavioral phenotypes in adulthood. Our data supports the hypothesis that Nr3c1 influences DNA methylation at birth and that DNA methylation in placenta correlates with adult frontal cortex DNA methylation and anxiety-like phenotypes.
Gesehen am 20.09.2021